Pedestrian and evacuation dynamics - Peacock, Richard D.; Kuligowski, Erica D.; Averill, Jason D. (Springer, 2011)
An aging population, increasing obesity and more people with mobility impairments are bringing new challenges to the management of routine and emergency people movement in many countries. These population challenges, coupled with the innovative designs being suggested for both the built environment and other commonly used structures (e.g., transportation systems) and the increasingly complex incident scenarios of fire, terrorism, and large-scale community disasters, provide even greater challenges to population management and safety. Pedestrian and Evacuation Dynamics, an edited volume, is based on the Pedestrian and Evacuation Dynamics (PED) 5th International 2010 conference, March 8th-10th 2010, located at the National Institute of Standards and Technology, Gaithersburg, MD, USA. This volume addresses both pedestrian and evacuation dynamics and associated human behavior to provide answers for policy makers, designers, and emergency management to help solve real world problems in this rapidly developing field. Data collection, analysis, and model development of people movement and behavior during nonemergency and emergency situations will be covered as well.